Changes in impact signals and muscle activity in response to different shoe and landing conditions - Wang, X.; Zhang, S.; Fu, W. (Journal of Human Kinetics, 2017)
Few rigorous scientific studies have investigated how the corresponding neuromuscular activity in the lower extremity occurs during different landing control movements in response to different impact signals. This study aimed to determine the potential shoe effects on impact signals, neuromuscular responses and their possible interactions in different human landing movements. Twelve male basketball players were required to wear high-cushioned basketball shoes (BS) and minimally cushioned control shoes (CC) to perform active drop jump landings (DJL) and passive landings (PL). Ground reaction forces and EMG amplitude (root mean square, EMGRMS) of the leg muscles within 50 ms before and after the landing movements were collected simultaneously. No shoe effect was found on the characteristics of impact signals and neuromuscular activity during the contact phase of DJL. By contrast, for PL, the values of maximal ground reaction force and the peak loading rate were evidently lower in the BS condition than in the CC condition (p < 0.05). Meanwhile, the EMGRMS of all muscles demonstrated a significant decrease in the BS condition compared with the CC condition within 50 ms after contact (p < 0.05). These findings suggest that under the condition in which related muscles are activated improperly, a neuromuscular adaptation occurs in response to different impact signals.